Designing Mobile Learning Media for Enhancing Creative Writing Skills - Ernalida Ernalida; Santi Oktarina (STAI Hubbulwathan Duri, 2024)
This study explores the practicality of mobile learning-based media in enhancing creative writing skills among junior high school students in Palembang City. The research aims to assess teachers’ and students’ perceptions of its practicality. This research represents the small group testing phase of a larger research and development project. Data were collected through questionnaires and interviews with teachers and students to gather qualitative and quantitative insights regarding the use of mobile learning media in creative writing instruction. The findings indicate that mobile learning-based media for creative writing is perceived as practical by both teachers and students. Assessments focused on material quality, language use, and media presentation aspects, all of which were rated highly feasible by participants. The results underscore the potential of this media to facilitate creative writing in junior high schools. The positive perceptions from small group testing suggest that mobile learning-based media provides an effective and user-friendly tool for improving creative writing skills. Teachers highlighted the relevance of the materials, while students appreciated the engaging and accessible format, supporting its integration into classroom practice. Mobile learning-based media demonstrates strong practicality in creative writing instruction for junior high schools in Palembang City. With its high feasibility ratings, it holds promise for broader implementation to support creative writing skills development. Future studies could explore its long-term impacts on student creativity and academic outcomes.